A Patient with Benign Lung Leiomyomatosis: Are There Any Difficulties in Diagnosis and Management? - O. A. Kirnosova; N. A. Karoli (Архивъ внутренней медицины)
The article presents a clinical observation of a 48-year-old patient who applied to the Department of pulmonology in connection with accidentally detected focal formations in the lungs during a preventive examination. In the presented clinical case, the patient’s disease was asymptomatic for a long time, for the first time, focal formations in the lungs were identified in 2020 and only a year later non-specific symptoms joined. Despite multiple consultations with narrow-profile specialists and the implementation of visualization methods of examination, the diagnosis of «lung leiomyomatosis» was made only four years later after a three-fold revision of histological blocks and the exclusion of other causes of focal pulmonary dissemination. This clinical case demonstrates a rare pathology and the complexity of differential diagnosis that doctors of all specialties may encounter. The features of the disease and the complexity of differential diagnosis determine the necessity of a multidisciplinary approach to the treatment of patients with this pathology.